2009
DOI: 10.1111/j.1399-5448.2009.00541.x
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of Glo-3A antibody levels in children at increased risk for type 1 diabetes mellitus

Abstract: Aims-To determine whether Glb1 homologue antibodies are associated with islet autoimmunity (IA) in children at increased risk for type 1 diabetes (T1D), and to investigate their relation with putative environmental correlates of T1D.Methods-We selected a sample from the Diabetes Autoimmunity Study in the Young (DAISY), a prospective study of children at increased risk for T1D. Cases were those who were positive for insulin, glutamic acid decarboxylase (GAD), or insulinoma-associated antigen-2 (IA-2) autoantibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…T1D patients have antibodies against different wheat proteins in the absence of CD. 48,49 Although it could be taken as a secondary phenomenon related to increased intestinal permeability, recent studies concerning immunological crossreactivity between wheat proteins and self-proteins in T1D 50 suggest that autoimmune reactions to unknown antigenic proteins in intestinal mucosa might also be involved in small-bowel mucosa destruction in some T1D patients.…”
Section: Discussionmentioning
confidence: 99%
“…T1D patients have antibodies against different wheat proteins in the absence of CD. 48,49 Although it could be taken as a secondary phenomenon related to increased intestinal permeability, recent studies concerning immunological crossreactivity between wheat proteins and self-proteins in T1D 50 suggest that autoimmune reactions to unknown antigenic proteins in intestinal mucosa might also be involved in small-bowel mucosa destruction in some T1D patients.…”
Section: Discussionmentioning
confidence: 99%
“…These comprise autoimmune diseases, including T1D (107,117,149,163), CD (45,46,51,126), multiple sclerosis (124,176,184), and rheumatoid arthritis (52), in which intestinal TJs allow the passage of antigens from the intestinal milieau, challenging the immune system to produce an immune response that can target any organ or tissue in genetically predisposed individuals (1,13,57,58,70,151). TJs are also involved in cancer development, infections, and allergies (32,55,57,147).…”
Section: Intestinal Permeability and Diseasementioning
confidence: 99%
“…More recently, we reported a direct link between antibodies to Glo-3a (a wheat-related protein), zonulin upregulation, and islet autoimmunity (IA) in children at increased risk for T1D (148). Sera from 91 IA positive cases and 82 controls were analyzed.…”
Section: Zonulin and Intestinal Barrier Functionmentioning
confidence: 99%
“…Simpson et al compared the levels of antibodies to a wheat storage globulin homologue of Glo-3A, which is a non-gluten component of the wheat protein matrix. They have shown that in children with islet auto-immunity, the antibody titer was directly linked to the early introduction of gluten, and inversely to breastfeeding duration [87]. Not all authors agree with this association; a prospective analysis from the DIPP study did not show a correlation between early or late introduction of gluten and subsequent development of pancreatic β-cells autoimmunity [88].…”
Section: Introduction Of Glutenmentioning
confidence: 80%